Analisis Sentimen Komentar Pengguna Aplikasi SAMBARA di Google Playstore - Muhammad Furqon Mulyaddin; Muhammad Ramadhan Mahendra; Muthia Dewi Rabbani (UIN Sunan Gunung Djati Bandung, 2024)
In the current era of globalization, there are numerous aspects that can be utilized by all humankind, particularly in harnessing technological advancements, one of which is in the field of governance, especially public services. One of the public services that can leverage technological progress is the Samsat service. One of its applications is the creation of the SAMBARA Application (Samsat Mobile for West Java). The SAMBARA Application represents a technological innovation aimed at facilitating access and financial management for its users. With a range of provided features, this application offers practical solutions in managing financial transactions, making payments, and providing up-to-date information regarding financial matters. This article aims to optimize the integrated system within the Sambara application to enhance the quality of services to a more superior level. The system development method encompasses a thorough analysis of user needs, technological infrastructure upgrades, and enhancement of application functionality. Research results indicate that through the implementation of this strategy, the Sambara application can provide more efficient, responsive services, consequently enhancing user satisfaction. System optimization within the Sambara application is a crucial step toward achieving the superior service standards expected by users.